Fabrication and Characterization of Black GaAs Nanoarrays via ICP Etching - Jing Ma; Yongqiang Zhao; Wen Liu; Peishuai Song; Liangliang Yang; Jiangtao Wei; Fuhua Yang; Xiaodong Wang (Nanoscale Research Letters, 2021)
Abstract GaAs nanostructures have attracted more and more attention due to its excellent properties such as increasing photon absorption. The fabrication process on GaAs substrate was rarely reported, and most of the preparation processes are complex. Here, we report a black GaAs fabrication process using a simple inductively coupled plasma etching process, with no extra lithography process. The fabricated sample has a low reflectance value, close to zero. Besides, the black GaAs also displayed hydrophobic property, with a water contact angle of 125°. This kind of black GaAs etching process could be added to the fabrication workflow of photodetectors and solar cell devices to further improve their characteristics.